Efektifitas Sistem Komputerisasi Pada Kinerja Pegawai di Kecamatan Sonder - Najoan, Olivia Nova; Lengkong, florence Daicy; Tulusan, Femmy (Sam Ratulangi University, 2015)
Abstract: The development of science and technology is very rapid had an impact on all activities undertaken by the organization. One of the technologies that can help in the work in the organizational environment is to use the computerized system. By using the a computerized system, then each unit office work can improve the effectiveness and efficiency of time.This study aims to determine how the effectiveness of computerized system in the performance of employees at the District Office Sonder. Before and after the use of computerized system. The study was conducted by obsevasing to the use of computerized system and their effect on the performance with in depth interview methods to obtain as much information from all respondents/informants. The number of informants is 14 people divided into camat secretary, head of section, an employee, who has exprerience in their respective duties, know in depth and a greater role in the process of using computerized system.Based on the results of the study, showed that the use of computerized system which is one of the facilities in order to smooth the working task, proven to provide convenience, many advantages and benefits that really support task this means employees have a positive aspect for all parties so that the effect on employee performance and can improve the quality of work and efficiency of time.Keywords : Computer Systems, Employee Performance